G214(P) Blended food for enteral feeding via a gastrostomy. (27th April 2015) - Brown, SJ
Abstract : A blended diet for enteral nutrition is defined as home-made everyday food blended to a smooth "single cream" consistency. Currently blended food is not recommended by the British Dietetic Association as a first choice supporting guidance on enteral feeding from N. I. C. E. However in a UK children's hospice the policy is where possible to replicate the care received at home, respecting parents' wishes. Therefore guidelines needed to be created for its use in the hospice. Benefits in physical and emotional health needed to be balanced against risks in tube blockage, contamination and digestive upsets. Aim was to gather information and risk assess the processes in order to formulate guidelines on the use of blended food for staff and parents. The process involved searches for information on the internet and liaising with specialist groups of dieticians and tube manufacturers. For the process of syringing/plunging where there is very little information available a visual demonstration was developed using a plastic box and a gastrostomy button. For issues relating to contamination and food hygenine we used exsisting guidance on food preparation. Guidelines were developed and presented to our clinical governance group for consideration and acceptance for use. Working with local dieticians a package of information including all the considerations and risks where developed to give to parents. Blended food is not recommended as a primary choice for enteral feed and may not be supported by all those involved in a childs care such as schools or respite unit. Blended diet is used by 10% of the tube fed children using our service. With careful consideration we have been able to develop practical guidelines that support and replicate care given at home whilst respecting the choices made by all our families on how their children are feed. For the future one UK university has started research to look at the health, social benefits and implications of blended diet. In North America where there are prescription costs and strict insurance schemes many opt for blended food, for others this is simply their preferred method. Here a company has developed a shelf safe product for gastrostomy feeding from "real food" available on Amazon.com